Pengaruh Social Network Marketing (Snm) Dan Electronic Word Of Mouth (Ewom) Terhadap Minat Beli Pelanggan - Wenny Kartika Susanto dan Keni (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Competition that is getting more competitive in smartphone industry has made customers feel quite difficult in deciding which product the customers should buy. This is because companies are doing marketing through mass media, both offline and online. Companies are trying to change customers’ way of thinking through emotion, need, want, and demand. Nowadays, in this globalization the traditional retailers are facing big challenge because young generation is starting to switch to online shopping. This fact poses as threat for traditional retailers, but can also be used as opportunity due to easy access to product and brand via social media. Therefore, this research objective was to find what the influences of social network marketing and electronic word of mouth (independent variables) toward customer purchase intention (dependent variable). Quantitative research was chosen as the method of this research. The population was smartphone users from 26 – 50 years old in Jakarta. Non – sampling method, specifically convenience sampling was used because this method allowed researched to approach random respondent easily. The researcher used 166 questionnaires as sample size. 166 valid data were analysed with Structural Equation Modelling to test hypothesises in the research. There are two hypothesises tested on this research. Based on analysis, all hypothesises are supported. In conclusion, the most significant value is Social Network Marketing (SNM) which contributed 35.3% toward purchase intention. Based on findings, it is suggested for the company to pay more attention in marketing activities at social media by giving positive experience to customers so that the customers can give positive feedback in social media as reference for future customers.